Biopsy interpretation of bone and bone marrow : histology and immunohistology in paraffin and plastic - Frisch, Bertha; Bartl, Reiner; Rothman, R (Arnold, 1999)
This fully revised and updated second edition builds on the features of its successful predecessor with high quality photomicrographs, descriptive text and key references. In addition it has a number of new features:
Keywords: Bone Marrow; Dřeň kostní; Biopsy; Histologie; kostní dřeň; biopsie; histologie